2000
DOI: 10.1161/01.atv.20.1.259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ω-3 Fatty Acids and Simvastatin on Hemostatic Risk Factors and Postprandial Hyperlipemia in Patients With Combined Hyperlipemia

Abstract: Abstract-Patients with combined hyperlipemia have lipid abnormalities associated with an increased tendency to develop atherosclerosis and thrombosis. This tendency may be accelerated during postprandial hyperlipemia. In the present double-blind parallel study, 41 patients with combined hyperlipemia and serum triacylglycerols between 2.0 and 15.0 mmol/L and serum total cholesterol Ͼ5.3 mmol/L at the end of a 3-month dietary run-in period were treated with simvastatin at 20 mg/d for at least 10 weeks; patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 45 publications
(39 reference statements)
4
61
2
Order By: Relevance
“…On the contrary, the PAI-1 activities decreased significantly. Both increased and decreased PAI-1 activities after fat loads have been reported (39,(42)(43)(44)(45)(46)(47). The difference in the postprandial PAI-1 responses has been explained by different genotypes of PAI-1, different fat types and content, and that PAI-1 has a circadian rhythm (PAI-1 concentrations decrease during the day) (39,44,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the PAI-1 activities decreased significantly. Both increased and decreased PAI-1 activities after fat loads have been reported (39,(42)(43)(44)(45)(46)(47). The difference in the postprandial PAI-1 responses has been explained by different genotypes of PAI-1, different fat types and content, and that PAI-1 has a circadian rhythm (PAI-1 concentrations decrease during the day) (39,44,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, 31 apparently healthy men, aged 45 -65 y, volunteered to participate in the intervention study. Following a lifestyle and biochemical screen, 15 volunteers satisfied the following inclusion criteria: non-smokers, with a habitually low intake of fish (n-3 polyunsaturated fatty acids have previously been shown to lower postprandial factor VIIa; Nordoy et al, 2000) and a body mass index (BMI) of between 20 and 33 kg=m 2 . None of the volunteers was adhering to any form of special diet or taking dietary fatty acid supplements.…”
Section: Subject Selectionmentioning
confidence: 99%
“…110 Across clinical studies, omega-3 fatty acids did not show a consistent effect on hemostatic variables including levels of fibrinogen, factor VII or VIII or von Willebrand factor. 60,111 Moreover, changes in levels of fibrinogen, factor VII or VIII, or von Willebrand factor generally did not significantly differ between recipients of 1000-6000 mg/day omega-3 EE and controls in healthy volunteers, 112 post-MI patients, 110 patients with mild hypertension, 81 patients with combined hyperlipidemia 109 or patients undergoing coronary artery bypass graft (CABG) surgery. 113 Bleeding time was prolonged in 40 post-MI patients after four weeks of 3400 mg/day EPA-DHA, without significant alteration of other hemostatic parameters, 114 and increased in one study in CAD patients.…”
Section: Dovepressmentioning
confidence: 94%
“…107 In patients with CAD, fibrinolytic activity, as assessed by plasminogen activator inhibitor-I activity levels, was found to be increased by 1800 mg/day of EPA, 108 and by EPA-DHA 3400 mg/day. 109 A three-month randomized study comparing 850 mg/EPA-DHA with usual care in 77 post-MI patients showed no differences in levels of …”
Section: Thrombosis and Hemostasismentioning
confidence: 99%